THE EFFECT OF TECHNOLOGY APPLICATION IN DIGITAL SUPPLY CHAIN ON COMPANY OPERATIONAL PERFORMANCE - Rahayu Rahayu; Wahyuningsih Santosa; Triwulandari Triwulandari (SEAN Institute, 2023)
Technology development today is increasingly rapid in various aspects of human life activities. This allows everyone to access various information easily and quickly through the internet. Technology is also applied to organizations or enterprises for operational effectiveness and efficiency. This study aims to study the influence of digitalization, supply chain management, and technology implementation in the digital supply chain on quality, Productivity, and cost reduction in aspects of operational performance. This research uses quantitative methodology and data from various industries that apply digital supply chains. Data from a survey of 162 respondents were analyzed using the Partial Least Square (PLS)-based SEM method. Research reveals that digitalization, supply chain management, and technology implementation in the digital supply chain positively influence quality, Productivity, and cost reduction in operational performance.